2018
DOI: 10.18203/issn.2454-5929.ijohns20184179
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of 100 cases of hoarseness of voice: a hospital based study

Abstract: <p class="abstract"><strong>Background:</strong> Hoarseness is defined as roughness of voice resulting from variations of periodicity or intensity of consecutive sound waves. Hoarseness is a symptom not a disease.</p><p class="abstract"><strong>Methods:</strong> The present study was carried out in the Department of ENT and Head and Neck Surgery, SMGS Hospital, Jammu over a period of 2 years from March 2016 to February 2018. During this period the patients who presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…at el 2018 (56%) and Gupta A at el 2018 (16%). 7 The result is very similar to our study. Vocal nodule was present in 22.22% cases in our study.…”
Section: Discussionsupporting
confidence: 91%
“…at el 2018 (56%) and Gupta A at el 2018 (16%). 7 The result is very similar to our study. Vocal nodule was present in 22.22% cases in our study.…”
Section: Discussionsupporting
confidence: 91%
“…The results are consistent with the studies by Vengala et al, 4 Rao et al, 5 and Pal et al 10 While in study by Gupta and Jamwal, 31% of housewives and 30% of businessman were most affected group. 8 In a retrospective study of Banjara et al, housewives (19.52%) were the largest group of patients affected by hoarseness of voice followed by laborer (17.53%), farmers (17.53%), and private job/businessman (15.94%), respectively. 11 In the present study, duration of hoarseness ranged from 2 days to 3 years.…”
Section: Discussionmentioning
confidence: 96%
“…This correlates with the study by Goswami et al 6 and Rathi and Sharma. 7 Gupta and Jamwal et al 8 found majority of patients (20%) in fifth decade. Also, in Kiakojoury et al study, highest prevalence of voice disorders was found in patients of age <45 years.…”
Section: Discussionmentioning
confidence: 96%
“…Vocal nodules are the most common lesion (11.95% cases) in a study by Hansa et al and in a study done by Gupta et al vocal nodule was the most common lesion comprising 30% of patients. 7,17 Another study showed that the incidence of vocal nodules was 12.72%. 11 A study done by Vengala et al showed that the common etiologies for voice change were acute laryngitis (30.82%), chronic laryngitis (19.86%), and vocal nodules (12.32%).…”
Section: A B C Dmentioning
confidence: 99%